Evaluation of serum mineral micronutrients (Zn, Cu, Fe, Mg) and their correlation with clinical parameters (gingival index, probing pocket depth, clinical attachment loss) in chronic periodontitis patients - Anusree Raju; Sanjeev Ravindran; Shyamala Devi MP; Shaheena KP; Anusha Anish; Hari S Pillai; Annamala PT (Asian Journal of Medical Sciences, 2023)
Background: Nutrition especially micro-mineral nutrients plays a major role in the etiology of chronic periodontitis. Serum levels of micro-mineral nutrients can be used as markers for the incidence of periodontitis and may also be used as indicators for dietary supplementation. Aims and Objectives: The aim of the study was to estimate the serum levels of Zn, Cu, Fe, and Mg of chronic periodontitis patients and normal healthy controls., to measure the clinical parameters (gingival index, probing pocket depth [PPD], and clinical attachment loss) in chronic periodontitis patients and normal healthy controls., to compare the levels of serum Zn, Cu, Fe, and Mg levels of chronic periodontitis patients and healthy controls and to correlate the levels of serum micronutrients with clinical parameters (gingival index, PPD, and clinical attachment loss) in chronic periodontitis patients and healthy controls. Materials and Methods: A total of 110 subjects, 55 subjects with chronic periodontitis and 55 healthy control subjects in the age group 35–65 years were selected for the study. Serum micronutrient levels of Cu, Fe, Zn, Mg, and the clinical parameters were measured. Results: Serum concentrations of Cu and Fe showed statistically significant increase and serum Zn and Mg showed a significant decrease in peridontitis patients as compared to normal healthy controls. Copper and Fe showed a significant positive correlation and Zn and Mg showed a significant negative correlation with clinical parameters (gingival index, PPD, and clinical attachment loss). Conclusion: The present study supports and extends the view that the assessment of serum mineral micronutrient can serve as possible biomarkers or indicators for an inflammatory condition like chronic periodontitis.